Prediction of SPT Value Based on Cone Penetration Test at Intake Water Project of Wolo River, Southeast Sulawesi - Uniadi Mangidi; Anafi Minmahddun; Edward Ngii; Rini Sriyani; Sulha (Indonesian Geotechnical Journal, 2023)
Soil investigation plays an important role in construction design. Adequate information regarding soil types and parameters are needed for a safe and economical foundation. However, limited budget often leads to inadequate soil investigations, and as a result, unknown soil parameters are estimated through correlations from the limited investigations that have been carried out. Correlations from SPT and CPT results are often used for design, but their applicability from location to location is questionable. This paper discusses the correlation of N-SPT values to CPT values in Wolo District, Kolaka Regency. The correlation was performed using linear regression analysis to obtain relationships between N-SPT and CPT. The three correlations obtained are N-SPT = 5.64 + 0.012qc, R2 value of 0.082; N-SPT = 5.93 + 0.01 qc – 0.095qf, R2 value of 0.125; N-SPT = 0.025qc + 0.341qf, R2 value of 0.455.